Empowering the future mothers: a bottom up approach - Vyas, Shaili; Aggarwal, Pradeep; Singh, Sadhna; ., Deepshikha; Kakkar, Rakesh; Kandpal, S. D. (International Journal Of Community Medicine And Public Health, 2017)
Background: In India, marriage at an early age is still common and unfortunately any institution does not provide any education either regarding safe maternal health and infant care. The first two years of child are very crucial for infant development and it is quite evident that the well-being and nutrition of the child and his or her future is totally dependent upon the knowledge of the mother that she has about child care. The aim of the study was to evaluate the awareness of breastfeeding amongst young female students from three different teaching institutions i.e. school, nursing and medical and to evaluate the influence of educational intervention on them. Methods: Dehradun has total 6 blocks of which 1 block was selected randomly i.e. CBD Doiwala. For selection of school, one school was randomly selected from the list of schools under CBD Doiwala. Out of 75 schools going young females 71 participated in the study. 66 Students each of 3rd Year Nursing and 3rd Year MBBS students of HIMS participated in the study. Results: In school girls scaling of awareness was maximally seen in average duration of breastfeed (35%) and adequacy of each breastfeed (27%). In nursing students scaling was maximum in awareness regarding breastfeeding a baby in HIV/TB infected mother (85%) and positioning of baby (52%), similarly, in medical students also, it was maximum in HIV/TB infected mother (81%) and positioning of baby during feeding (48%). Conclusions: Educational intervention is an effective tool to improve awareness regarding breastfeeding practices.